A Laser Scanning Method to Control the Location, Shape, Contact Angle and Sliding of Water Droplet on Superhydrophobic Surface. Issue 7 (9th April 2019) - Zhang, Hui; Liu, Yang; Hua, Meng; Dong, Guang‐Neng
Abstract : A simple and novel approach is proposed to control location, shape, contact angle, and sliding of droplet on superhydrophobic aluminum alloy surfaces scanned by laser. By firstly etched suitably, followed by coating with stearic acid, aluminum alloy surface is possible to exhibit the property of superhydrophobic behavior. Irradiating such surface with specific hydrophilic patterns, by a relatively high power and precisely controlled laser, allows fixing the location and shape of water droplets. Suitably altering scanning time and power of the laser beam, the fabricated surface facilitates the control of the contact angle of droplet. Properly railing hydrophilic lines/curves on such superhydrophobic surface facilitates constraining droplet to slide and water to flow in certain controllable orientations. Furthermore, relevant likely mechanisms involved in controlling the location, shape, contact angle, and sliding of water droplet on hydrophobic/hydrophilic surface have also been elucidated systematically on the basis of analyzation of electrical scanning images. Abstract : A laser scanning approach is proposed to control location, shape, contact angle, and sliding of droplet on aluminum alloy. Suitably altering scanning time and power of laser facilitates control of the contact angle of droplet. Irradiating superhydrophobic surface with hydrophilic patterns allows fixing the location and shape of droplets and also allows constraining droplet to slide in certain controllable orientations.